1969
DOI: 10.1111/j.0954-6820.1969.tb12744.x
|View full text |Cite
|
Sign up to set email alerts
|

I. The Chemical Composition of the Fat Emboli in the Post‐absorptive Dog

Abstract: Abstract. Pulmonary fat emboli were isolated in 7 post‐absorptive dogs after bone fracture. The emboli consisted mainly of triglycerides. The fatty acid composition of these triglycerides was compared with that of plasma and bone marrow triglycerides. The triglycerides in the emboli were similar to those from bone marrow but differed from those in plasma. These observations indicated that the bone marrow fat is the source of the embolised fat in the lungs in the case of trauma. It was also concluded from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

1969
1969
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…In previous investigations the chemical composition of pulmonary fat emboli was analysed in traumatized fasting dogs. A similarity was found between the fatty acid composition of bone marrow and the emboli triglycerides in thwe dogs (5,7). These observations indicated that fat emboli, developing during a nutritional state with a low amount of Iriglyceride-rich Iargc lipoproteins, originate from and consist almost entirely of bone marrow triglycerides.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…In previous investigations the chemical composition of pulmonary fat emboli was analysed in traumatized fasting dogs. A similarity was found between the fatty acid composition of bone marrow and the emboli triglycerides in thwe dogs (5,7). These observations indicated that fat emboli, developing during a nutritional state with a low amount of Iriglyceride-rich Iargc lipoproteins, originate from and consist almost entirely of bone marrow triglycerides.…”
mentioning
confidence: 81%
“…Dogs RC1, CC1 and CC2 were used as non-traumatized controls. The experimental procedures, the isolation of the emboli, the chemical and histological analyses were performed as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three post-absorptive dogs were traumatized as described previously (5) and the fat emboli subsequently isolated.…”
Section: Methodsmentioning
confidence: 99%